Utilization of Metallurgical Wastes and Using in Portland Cement Industry - Bakhriev, N. F.; Omonov, A. O. (European Journal of Life Safety and Stability (2660-9630), 2022)
Metallurgy is essential for socioeconomic development, and the process discharges waste containing a variety of toxic and hazardous compounds. This paper aims to provide Recycle, Reduce and Reuse to manage metallurgical wastes. The rapid development of metallurgical industry, leads to large amount of metallurgical solid waste. The slag, dust and sludge generated by integrated steel plants were called waste. These wastes contain some valuable resources and elements such as iron, zinc, lead, calcium, etc., which can be reused in Portland cement making process or can be used as raw materials therefore the term waste has been replaced with by-product due to intensive re-utilization of these wastes. The authors made an attempt to implement the idea by using the local iron scale of the Tashkent Metallurgical Plant as a ferrite additive during clinker firing. The joint venture Tashkent Metallurgical Plant is a super modern enterprise of New Uzbekistan, with an annual capacity of 500 thousand tons of cold-rolled steel with galvanized and polymer coating.